PENINGKATAN PEMBANGKIT LISTRIK TENAGA PIKOHIDRO (PLTPH) : PEMANFAATAN, DAYA LISTRIK DAN DISTRIBUSI LISTRIK - Hari Prasetijo; Purwanto Bekti Santoso; Ari Fadli (Universitas Jenderal Soedirman, 2020)
The purpose of this activity is to increase the utilization of existing picohidro power plants (PLTPH), increase the power capacity and quality of existing PLTPH and improve the quality of electricity distribution for public street lighting in Siwarak hamlet, Watuagung village, Tambak district, Banyumas district. The achievement of the objectives of the activity is carried out by the methods of: (1) making training dictates, (2) training of facilitators, (3) training of elementary school age children and facilitating laptops and printers (4) increasing the capacity of power plants for picohydro and power plants, and (5) improving the quality of electricity distribution.The results achieved were: computer training for 25 children of primary education age, 4 facilitators, an increase in PLTPH power from 1000 watts to around 1500 watts, an increase in the quality of generating houses and an increase in the quality of electricity distribution for public street lighting.Keywords : improvement, utilization, quality, PLTPH, lighting